Geschichte und Leben eines Textes: Über die Erklärung Zur Problematik der Aussiedlung der Sudetendeutschen aus 1995 - Ladislav Beneš (Communio Viatorum)
The article recalls the publication and historical context of the Declaration on the Question of the Expulsion of the Sudeten Germans, which was adopted as an official statement by the Evangelical Church of Czech Brethren (ECCB) in 1995. The document dealt with the past and present of relations between Czechs and Germans, in particular with the expulsion of the Sudeten Germans from the Czechoslovak border regions after the Second World War. The ECCB’s declaration was intended to express the fact that the two nations caused each other considerable harm during this period. However, a common future is only possible through mutual reconciliation, forgiveness and a joint endeavour to overcome historical injustice. The creation of the declaration was a reaction to the context at the time, when the aim was to find a new way of co-operation between Czechs and Germans after the revolution of 1989. After forty years of communist rule in Czechoslovakia, mutual antipathy was once again widespread among the public. The Sudeten German Landsmannschaft was a key group in this respect. The authors of the Declaration on the Question of the Expulsion of the Sudeten Germans faced criticism, mainly because of historical inaccuracies or an alleged unnecessary humiliation of the Czechs towards the Germans. Nevertheless, the document was largely favourably received by the public and politicians and was gratefully received by the Evangelical Church in Germany (EKD). Subsequently, the declaration was taken as inspiration for further work on the topic and, in cooperation with the EKD, a Protestant anthology on the subject was produced.